A CARE-compliant article: Unicentric Castleman disease presenting as a retroperitoneal mass of the upper edge of the pancreas. Issue 11 (March 2020) - Zhou, You-Xin; Ji, Yong; Wu, Sheng
Abstract: Rationale: Castleman disease (CD) is a rare lymphoproliferative disease with a poorly understood etiology. The occurrence of CD in the abdominal cavity is very rare, especially in the retroperitoneal peripancreatic region. Patient concerns: A 33-year-old woman was referred to our department on March 1, 2018 for a detailed physical examination due to retroperitoneal peripancreatic lymph node enlargement over 15 days. Diagnosis: Enhanced magnetic resonance imaging of the epigastrium showed the mass with abundant blood supply is located between the liver and the stomach in the upper margin of the pancreas. Postoperative pathological examination revealed CD, type of unicentric Castleman disease. Interventions: We performed an open surgery on this patient and completely removed the mass. There was no postoperative radiochemotherapy. Outcomes: The patient was followed-up for more than 12 months after the operation and showed good recovery. Lessons: CD is a rare disorder that is hard to diagnose early and complete resection of the tumor is still the most effective treatment.